Fixed Costs Matter - Jurjen Kamphorst; Ewa Mendys-Kamphorst; Bastian Westbrock (Tinbergen Institute, 2018)
According to standard economic wisdom, fixed costs should not matter for pricing decisions. However, outside economics, it is widely accepted that firms need to increase their prices after a fixed cost rise. In this note, we show that a liquidity-constrained firm that maximizes lifetime profits should increase its price after a fixed cost increase, if future profits depend positively on current sales. The reason is that then the optimal price is lower than the one that maximizes the current profit. Because the higher cost necessitates higher current profits to avoid bankruptcy, the firm needs to increase its price.
Keywords: D42; L11; 330; fixed costs; sunk costs; brand loyalty; switching costs; pricing